Examining long-term repetition priming effects in spoken word recognition using computer mouse tracking - Tuft, Samantha E.; Incera, Sara; MᶜLennan, Conor T. (Frontiers in Psychology, 2023)
Language researchers in a variety of disciplines have used priming as a tool to investigate theoretical questions. In spoken word recognition, long-term repetition priming effects have been obtained across a number of behavioral tasks (e.g., lexical decision, shadowing). Repeated – primed – words are responded to more efficiently than new – unprimed – words. However, to our knowledge, long-term repetition priming effects have not been examined using computer mouse tracking, which would provide data regarding the time course of long-term repetition priming effects. Consequently, we compared participants' lexical decision responses using a computer mouse to primed and unprimed words. We predicted that participants would respond more efficiently to primed words compared to unprimed words. Indeed, across all of the dependent variables investigated (accuracy, reaction time, mouse trajectories) and across environments (in person, online), participants responded more efficiently to primed words than to unprimed words. We also performed additional exploratory analyses examining long-term repetition priming effects for nonwords. Across environments (in person, online), participants had more errors to primed nonwords than to unprimed nonwords, but there were no differences in reaction times and mouse trajectories. The current data demonstrating long-term repetition priming effects in mouse tracking are expected to motivate future investigations examining the time course of various long-term repetition priming effects for both words and nonwords.